The Strategic Role of Lembaga Adat Negeri in the Fulfilment of Victims’ Rights to Reparation in Post-Conflict Ambon - Nalesti Dewi, Trihoni; Kwik, Jonathan; Watloly, Aholiab (Udayana Journal of Law and Culture; Vol 1 No 2 (2017): Rights of the Vulnerable Groups, 2017)
This article demonstrates the strategic position of Lembaga Adat Negeri in the fulfilment of the long-neglected right to reparation of victims in post-conflict Ambon. Lembaga Adat Negeri were chosen as the object of analysis due to their close cultural affiliation with the Ambonese society. Due to the important role that Lembaga Adat Negeri play in local Ambonese governance, it is argued that they can assist in absorbing local aspirations and aid the reparation process. The recent enactment of Law No. 6 of 2014 concerning Desa provides Lembaga Adat Negeri with ever greater momentum to spearhead reconciliation based on Ambonese traditional values and contribute to the peaceful transition of the divided people, in particular by way of fulfilling the right to reparation of victims.